The Impact of Pretrial Juvenile Detention on 12-Month Recidivism: a Matched Comparison Study - Cusworth Walker, Sarah (Crime & delinquency, 2020)
Pretrial detention, the use of detention to ensure youth attend court hearings, makes up 75% of all juvenile detention admissions. Research investigating the impact of detainment on youth outcomes is limited and, when available, does not distinguish between different uses of detention. Consequently, little is known about the effects of detaining youth for this purpose. The current study examines the impact of pretrial detention on more than 46,000 juvenile cases across 32 jurisdictions. Using propensity score matching, analyses found that pretrial detention was associated with a 33% increase in felony recidivism and 11% increase in misdemeanor recidivism within one year, and a small effect for length of stay (1% increased risk per day). The analyses also revealed an interaction effect with prior criminal history indicating that this relationship shifts once a youth has a number of previous criminal filings.